Assessment of soybean yield using thermal indices - Sachin; Ashvathama, V H; Kiran, B O; Naidu, G K (Plant Science Today, 2026)
A field experiment was conducted at all India coordinated research project on soybean, Dharwad in 2022 to assess the performance of soybean cultivars in terms of thermal indices and yield components. Ten soybean cultivars including three checks were evaluated in a randomized block design. Significant genotypic variation was observed in Growing Degree Days (GDD), with DSb 23 and DSb 39 recorded the highest GDD from Flower Initiation (FI) to Physiological Maturity (PM). Phenothermal Index (PTI) showed a consistent slight increase during crop development, with DSb 39 having the highest PTI at maturity. Heat Use Efficiency (HUE) differed significantly among cultivars, with DLSb 5 recording the highest value. DLSb 5 recorded the highest seed yield (31.21 q/ha), followed by DSb 34. Significantly lowest yield (18.83 q/ha) was recorded in DLSb 1, which also showed the lowest HUE. Significant variation in the number of pods per plant was also found, with DLSb 5 recorded the highest number of pods. Yield was positively associated with the number of pods per plant. The findings highlight the potential of DLSb 5 and DSb 34 as promising cultivars under varied thermal environments. These findings highlight key traits that improve soybean yield.